Multistimuli‐Responsive Materials from Benzothiadiazole‐Based Charge‐Transfer Chromophores: Interdependence of Optical Properties and Aggregation. Issue 12 (20th September 2018) - Bardi, Brunella; Dall'Agnese, Chunxiang; Tassé, Marine; Ladeira, Sonia; Painelli, Anna; Moineau‐Chane Ching, Kathleen I.; Terenziani, Francesca
Abstract: A family of multipolar V‐shaped chromophores bearing an A′‐D‐A‐D‐A′ structure were investigated, where 2, 1, 3‐benzothiadiazole, acting as the central electron acceptor (A), is linked to two thiophene‐based electron‐donating moieties (D) end‐capped with alkyl‐cyanoacetate substituents (A′). The spectroscopic properties of thin films and powders were investigated and were compared to solutions and nanoaggregates. The optical properties strongly depended on the aggregation state and could be tuned by means of thermal treatment (annealing) of the films and through mechanical treatment (grinding) of the powders, demonstrating that these materials are multistimuli responsive. The spectroscopic analysis revealed the partial formation of J‐aggregates both in the films and in powders, despite the weak luminescence. This behavior was interpreted as due to the partial formation of poorly fluorescent red‐shifted aggregates acting as a sink in an efficient excitation energy‐transfer process from J‐aggregates. Abstract : Form an orderly queue ! The coexistence of different aggregated forms, including non‐fluorescent J‐aggregates, is found in films and powders of a family of organic chromophores. The abundances of these aggregrated forms can be varied upon the application of soft external stimuli.